Using data assimilation in mesoscale numerical modeling to map offshore wind resource - Fernandes, Miguel (2013)
data from GHRSST Level 4 analysis have been ingested to an atmospheric mesoscale numerical model using a Newtonian relaxation assimilation technique. The mesoscale model WRF was used to map the wind resource at 90 m a.g.l. for the North Sea area. A model domain with a spatial resolution of 20x20 km was used to simulate a winter and a summer month, November 2008 and July 2009. The modeled wind results have been validated against observational data from the anemometric mast FINO1. A spatial improvement of the average wind field at 90 m a.g.l. from the observational data has been assessed. Each assimilated data source has shown a distinct impact. The QS assimilation had higher impact during the summer period while the SST assimilation during the winter period. Improvements of 5% and more were obtained from using data assimilation on the overall domain. Validation with the FINO1 anemometric mast shows improvements on the average vertical wind profile while error statistical parameters were only slightly improved.